2021
DOI: 10.1088/1757-899x/1091/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aspect of material selection for substrate board equipped with high heat flux IC chips

Abstract: This paper investigates the material selection for substrate board equipped with nine silicon heaters that mimic IC chips. This includes computational research on laminar forced convection air cooling of silicon IC chips in electronic components mounted on substrate boards subjected to high uniform heat fluxes in a horizontal channel. Copper clad boards with single and multilayer having thermal conductivities of 8.8, 40.5, and 61.5 W/m K are the substrate materials used in this study. Three-dimensional steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They proposed artificial neural network as alternative tool to CFD. Durgam et al [13,14,15,16] have used machine learning algorithms viz. support vector regression, XG Boost, random forest regression, and artificial neural network as an alternative to simulation software for cooling of heaters with dummy components on PCB under forced convection.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed artificial neural network as alternative tool to CFD. Durgam et al [13,14,15,16] have used machine learning algorithms viz. support vector regression, XG Boost, random forest regression, and artificial neural network as an alternative to simulation software for cooling of heaters with dummy components on PCB under forced convection.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that flow in the fan-drawing system was steady and uniform, which could be simulated using a laminar flow model. Moreover, Durgam et al (2021) presented that the distribution of the temperature on RPCB strongly depends on the position of heaters, Reynolds number (Re), the thermal conductivity of RPCB.…”
Section: Introductionmentioning
confidence: 99%